Analysis of Village Government Efforts to Improve Public Services in Tanah Mea Village, West Kutai Regency - Einsbie Grata Myn; Muhammad Kasim; Ela Yusrianti (Formosa Journal of Applied Sciences, 2023)
This research aims to analyze the efforts of the Tanah Mea village government, West Kutai Regency in improving the quality of public services. The research method uses a case study approach to explore in order to obtain an interpretation of the "interpretive framework" analysis to see the local government's efforts involving several village officials. The results of the research show that there are technical and non-technical obstacles in implementation, such as: unclear explanation of village regulations (Perdes), minimum standards for village services, standard operating procedures, minimal village apparatus resources in the use of technology and information, disruption to general infrastructure and electricity network constraints and service efforts. Fulfillment of basic rights can be accepted by local communities even though there are limited village apparatus resources and facilities and infrastructure in providing administrative services.